2017
DOI: 10.1002/pmh.1373
|View full text |Cite
|
Sign up to set email alerts
|

The role of affective temperament as a predictor of relapse in alcohol dependence

Abstract: Our results provide new insights about the role of affective temperaments in alcohol use disorders, specifically in predicting short-term relapse in detoxified male alcohol-dependent patients. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…In response to the first aim of this study, which was to examine the relationship between the risk of substance addiction and the dimensions of temperament and attachment, we can confirm the correlation between the "novelty seeking" dimension and the risk of substance addiction, in line with the findings of other studies (Zilberman et al, 2013;Monras et al, 2008;Paulino et al, 2017). As observed in the aforementioned studies, we can also confirm that in our sample "Persistence" was the temperamental dimension to correlate most negatively with the risk of addiction.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In response to the first aim of this study, which was to examine the relationship between the risk of substance addiction and the dimensions of temperament and attachment, we can confirm the correlation between the "novelty seeking" dimension and the risk of substance addiction, in line with the findings of other studies (Zilberman et al, 2013;Monras et al, 2008;Paulino et al, 2017). As observed in the aforementioned studies, we can also confirm that in our sample "Persistence" was the temperamental dimension to correlate most negatively with the risk of addiction.…”
Section: Discussionsupporting
confidence: 89%
“…According to Cloninger's model, temperament has four independent innate and hereditary dimensions (Cloninger, 2008). Of these, several studies highlight "novelty seeking" as the one most related to disorders of substance abuse or addiction (Zilberman, Tavares, & El-Guebaly, 2003;Monras Arnau, Mondon, & Jou Santacreu, 2008;Paulino, Pombo, Ismail, Figueir, & Lesch, 2017); "Novelty seeking" would relate to behaviours of impulsivity and low frustration tolerance (Bagher Saberi Zafarghandi, Khanipour, & Ahmadi, 2018), which relate, at their time, to substance abuse and to relapse to this abuse (Paulino et al, 2017;Pérez de Albéniz Garrote et al, 2018). On the other hand, high scores on the "persistence" scale would be related to a lower risk of addiction (Monras et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that the neural circuitry involved in addictive behaviors is closely related to the circuitry of affective modifications . Many studies have focused on SUD and its relation with affective temperaments and how these temperaments are considered as risk or protective factors to this disorder . In a study on heroin addiction and the affective temperaments, which compared 59 stabilized methadone‐treated heroin addicts to 58 nonaddicts, the cyclothymic and the irritable temperament was present in addicted patients .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Many studies have focused on SUD and its relation with affective temperaments and how these temperaments are considered as risk or protective factors to this disorder. [11][12][13][14][15] In a study on heroin addiction and the affective temperaments, which compared 59 stabilized methadone-treated heroin addicts to 58 nonaddicts, the cyclothymic and the irritable temperament was present in addicted patients. 11 In another study on people with alcohol abuse, the cyclothymic temperament is the main trait present in addicted patients.…”
mentioning
confidence: 99%
“…To individualize treatment strategies, reliable markers to predict the outcome in alcohol‐dependent patients are needed. Although various parameters have been discussed (Bauer et al., ; Bottlender and Soyka, , b; Braun et al., ; Gegenhuber et al., ; Lenz et al., ; McKee and Weinberger, ; Paulino et al., ; Rubio et al., ; Weinland et al., , ; Wojnar et al., ), they are still not implemented in the clinical routine of patients undergoing withdrawal treatment because of their limited predictive power and applicability.…”
Section: Aims Of the Studymentioning
confidence: 99%